Dinamika Kehidupan Sosial Ekonomi Kota Tukang Ojek Online (GOJEK) - Chairun Niswa Simanullang; Yeshieca Ginting (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Abstrak. Transport used the society to facilitate daily activities. Everyone needs transportation in a variety of activities such as work, school, travel or other activities. Technological advances in the field of transportation, becoming the socio-cultural reality going on in the community, that the current internet is very influential to the citizens of the community in living the life the community. The rise of smartphone users, either the system android or iOS makes the community dependent on Smartphones and the internet. The opportunities for making business founder Taxi online (Go-Jek) is presenting an online-based.. The research method used was based on qualitative methods of study case as well as the collection of data is done with the techniques of observation, interview and documentation.. Online taxi exploited students not only deliver them home leave, but also to order food and supplies for academic purposes with rates that are relatively inexpensive.